Comparative Study on Chemical Composition of Green and Black Table Olives Brines of the Endemic ’’Sigoise’’ Cultivar: Recovery of high-Added Values Compounds - Mohamadi, N; Meraghni, M; NECIB, N; Jelaiel, L; El Arbi, M; Bouaziz, M (My University, 2023)
The effluents derived from the processing of table olives stand for a serious environmental problem. The study aims to valorize the brine water of table olives at different stages of ripening (green and black) of the Algerian variety Sigoise of Bejaia (East) and Mascara (West). The physico-chemical characterization revealed that these samples display have a high acid pH and salinity. The comparative study of phenolic levels exhibited showed very significant differences between the brine waters of green olives from Bejaia and Mascara, while the brines of black olives presented showed comparable levels. A high strong antioxidant potential was confirmed by DPPH (CI50=0.35 μg/100 ml–0.50 μg/100 ml) and FRAP (CI50=626.89 μg/100 ml–875.54 μg/100 ml) tests. Chemical screening by HPLC-DAD of the four samples identified high concentrations of hydroxytyrosol (HT) (390.4 mg/100 ml–360.8 mg/100 ml) and tyrosol (202.2 mg/100 ml–101.4 mg/100 ml). This study provided a deeper insight into the phenolic profile and the antioxidant potential of these brines